The polymerization of acetylene on supported metal clusters - Gilb, S.; Arenz, M.; Heiz, U. (Физика низких температур, 2006)
The polymerization of acetylene was studied by thermal programmed reaction on model catalysts consisting of size-selected Ag, Rh, and Pd atoms and Pdn (1 ≤ n ≤ 30) clusters on well-characterized MgO(111) thin films. In a single-pass heating cycle experiment, benzene, butadiene, and butane were catalyzed with different selectivities as function of cluster size: palladium and rhodium atoms selectively produce benzene, and the highest selectivity for butadiene is observed for Pd₆, whereas Pd₂₀ reveals the highest selectivity for butane. Ag atoms are inert. These results provide an atom-by-atom observation of the selectivity of small cluster catalysts.